دور البنـــــوك فـــــي محاربــــــة جريمـــــة تبييـــــض الأمـــــوال - نــــــــــــوال جوامـــــع; سلمـــــى مقـــــرود (My University, 2018)
Summary: The crime of money-laundering is one of the most significant economic crimes caused by globalization, especially financial globalization. It aims primarily at legitimizing illegally collected funds. Bleaching is carried out in many different ways and methods, primarily based on the banking system. The crime of money-laundering is one of the most serious forms of organized crime developed in today's society, as it affects both national and international security and economic prosperity, and they have therefore committed the international community to tackling and combating it in all ways and by all means. Since banks were the first destination for bleachers to launder and clean up their dirty money, the international community had made them a way to reduce that crime. It has concluded many international conventions such as the Basel Conventions and the International Financial Action Task Force. national legislation, including Algeria, had been established to monitor banks and combat crime. It also promulgated a series of laws through which banks and financial institutions have imposed a series of obligations, including the prohibition of whitewashing, which the breach exposes to disciplinary and criminal accountability. In doing so, it has made banks an important role in addressing and defining this crime. ............................... الملخص: تعـــــــد جريمة تبييض الأموال من أهم الجرائم الاقتصادية التي أفرزتها العولمة خاصة العولمة المالية، وتهدف أساسا إلى إضفاء الصبغة الشرعية على الأموال المحصلة بصفة غير شرعية وتتم عمليات التبييض بعدة طرق وأساليب مختلفة ترتكز بالأساس على النظام المصرفي. تعتبر جريمة تبييض الأموال من أخطر صور الجرائم المنظمة المستحدثة في مجتمعنا اليوم، إذ أنّها تمسى الأمن والرخاء الاقتصادي سواء على المستوى الوطني أو على المستوى الدولي، لذلك ارتان المجتمع الدولي إلى التصدي لها ومكافحتها بشتى الطرق وجميع الوسائل. وبما أن البنوك تعتبر الوجهة الأولى التي يتجه لها المبيضون من أجل غسل أموالهم القذرة وتنظيفها فإنّ المجتمع الدولي جعل منها سبيلا للحد من هذه الجريم. حيث عقدت العديد من الاتفاقيات الدولية مثل اتفاقيات بازل وما صدر عن مجموعة العمل المالي الدولي، وسارت على نهجها التشريعات الوطنية ومنها الجزائر، إذ شكلت مجموعة من الأجهزة للرقابة على البنوك ومحاربة الجريمة، كما أصدرت مجموعة من القوانين ألقت من خلالها على عاتق البنوك والمؤسسات المالية مجموعة من الإلتزامات منها الكاشفة ومنها المانعة لعمليات التبييض والتي يعرضها الاخلال بها إلى المساءلة التأديبية والجزائية. وبذلك نجد أنها قد جعلت للبنوك دورا هاما في التصدّي لهذه الجريمة ووضع حدّلها. ............................... Résume : Le crime de blanchiment d’argent est l’un des plus importants crimes économiques engendrés par la mondialisation et spécialement les échanges de capitaux, il vise à cacher l’origine d’une somme d’argent qui à été acquise par le biais d’une activité illégale en la réinjectant dans des activités légales et le blanchiment se fait à travers des méthodes différentes basées essentiellement sur le système bancaire. Le blanchiment d’argent est le plus dangereux parmi les crimes organisés, il favorise la corruption et déstabilise l’économie des payes vulnérables, pour cela la communauté internationale à décidé de lutter contre le blanchiment de l’argent à travers tous les moyens . La communauté internationnale à luttes contre le blanchiment d’argent auprès des banques et des paradis fiscaux. Ce qui a pousser à la conclusion de plusieurs convention internationale, comme : la convention de Basel et le groupe de travail financière international ; des législations nationales leurs ont suri et parmi eux il ya l’Algérie, dont elle à former w groupe des institutions pour la surveillante des banques et la lutte contre la civnonalité, elle a aussi posé des lois qui oblige les banques et les institutions financières à lutter contre le blanchiment sous peine d’une sanction pénale. Et à travers ça nous remarquons qu’ elle a dommée un rôle tres important aux banques pour lutter contre ce crime.